Heterostructure Films of SiO2 and HfO2 for High-Power Laser Optics Prepared by Plasma-Enhanced Atomic Layer Deposition - Alam, Shawon; Paul, Pallabi; Beladiya, Vivek; Schmitt, Paul; Stenzel, Olaf; Trost, Marcus; Wilbrandt, Steffen; Muehlig, Christian; Schroeder, Sven; Matthaeus, Gabor; Nolte, Stefan; Riese, Sebastian; et al. (Coatings, 2023)
Absorption losses and laser-induced damage threshold (LIDT) are considered to be the major constraints for development of optical coatings for high-power laser optics. Such coatings require paramount properties, such as low losses due to optical absorption, high mechanical stability, and enhanced damage resistance, to withstand high-intensity laser pulses. In this work, heterostructures were developed by sub-nanometer thin films of SiO2 and HfO2 using the plasma-enhanced atomic layer deposition (PEALD) technique. Thin-film characterization techniques, such as spectroscopic ellipsometry, spectrophotometry, substrate curvature measurements, X-ray reflectivity, and Fourier transform infrared spectroscopy, were employed for extracting optical constants, residual stress, layer formation, and functional groups present in the heterostructures, respectively. These heterostructures demonstrate tunable refractive index, bandgap, and improved optical losses and LIDT properties. The films were incorporated into antireflection coatings (multilayer stacks and graded-index coatings) and the LIDT was determined at 355 nm wavelength by the R-on-1 method. Optical absorptions at the reported wavelengths were characterized using photothermal common-path interferometry and laser-induced deflection techniques.
CRIS-Team Scopus Importer:2023-04-20
Keywords: antireflection coatings; hafnium dioxide; heterostructures; LIDT; low-loss coating; plasma-enhanced atomic layer deposition; silicon dioxide